PERSEPSI GURU TERHADAP PELAKSANAAN PROGRAM MAKAN BERGIZI GRATIS (MBG) DI SEKOLAH DASAR - Gretch Mach Lutherina Leobisa; Tritanty Sintikhe Manu; Kamelia Ongo Makin; Maria Faustina Kewa Saya; Adam Bol Nifu Benu; Habibi Musa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze teachers’ perceptions of the implementation of the Free Nutritious Meal Program (Program Makan Bergizi Gratis/MBG) at SD GMIT Oepura. The MBG program is a national policy initiated by the Indonesian government to improve students’ nutritional status, health, and learning readiness, as well as to reduce stunting among school-age children. This research employed a descriptive quantitative approach using a survey method. The subjects consisted of 19 elementary school teachers who were directly involved in and had adequate knowledge of the MBG program implementation. Data were collected through a closed-ended questionnaire using a Likert scale, which measured six main indicators: teachers’ understanding of the MBG program, program implementation, food quality and suitability, program impact on students, implementation constraints, and teachers’ attitudes and support toward the program. The collected data were analyzed using descriptive statistical techniques by calculating mean scores and categorizing them based on predetermined criteria. The results indicate that teachers’ understanding of the MBG program is categorized as “understand,” program implementation is perceived as “good,” and food quality and suitability are considered “appropriate” according to students’ nutritional needs. The program is also perceived to have a positive impact on students, particularly in improving health conditions and learning motivation. However, several challenges were identified, including limited food storage facilities, coordination issues among stakeholders, and potential disruptions to classroom learning activities. Despite these constraints, teachers demonstrate positive attitudes and strong support for the sustainability of the MBG program. These findings highlight the important role of teachers as key implementers of the program and emphasize the need for improved coordination, adequate infrastructure, and continuous evaluation to optimize the effectiveness and sustainability of the Free Nutritious Meal Program in elementary schools.